2022
DOI: 10.26582/k.54.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Is the relative age effect prevalent in elite Brazilian male futsal? An investigation based on age categories and playing positions

Abstract: This study aimed to investigate the existence of relative age effect (RAE) in male Brazilian futsal athletes according to age categories and playing position. Data from male futsal athletes from the top five teams in Brazil were collected during May and June 2021. The distribution of birth dates of 387 male futsal athletes was analyzed, based on their age categories (U15, n = 97; U17, n = 88; U20, n = 116; senior, n = 86) and playing positions (defender, n = 76; winger; n = 162; pivot, n = 69; goalkeeper, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
1
0
2
Order By: Relevance
“…These authors observed an overrepresentation of athletes born in the first quartile of the year (Q1 vs Q4) in the Under-9 female and the Under-7 and Under-9 male categories. Similar results were reported among Brazilian elite male athletes (Castro, et al, 2022b;Morales Júnior, Alves, Galatti, & Marques, 2017) from the Under-17, Under-20, and senior categories. Additionally, this effect seemed to differ based on the athletes' playing positions (Castro, et al, 2022a).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These authors observed an overrepresentation of athletes born in the first quartile of the year (Q1 vs Q4) in the Under-9 female and the Under-7 and Under-9 male categories. Similar results were reported among Brazilian elite male athletes (Castro, et al, 2022b;Morales Júnior, Alves, Galatti, & Marques, 2017) from the Under-17, Under-20, and senior categories. Additionally, this effect seemed to differ based on the athletes' playing positions (Castro, et al, 2022a).…”
Section: Introductionsupporting
confidence: 87%
“…Since RAE may influence a young athlete's opportunity to obtain better training and performance conditions to reach elite levels in sports (Leite, et al, 2021;Lidor, et al, 2021), further studies with specific populations in different sports are still needed. Although RAE arouses interest among many researchers and publications have increased in recent years, investigations in specific sports contexts being underrepresented in this research are warranted, particularly including futsal (Bilgiç & Işın, 2022;Castro et al, 2022bCastro et al, , 2022cLeonardi, et al, 2022). In fact, Méndez-Dominguez, Nakamura, and Travassos (2022) highlighted the importance of developing research on futsal, not only concerning physical, technical, or tactical variables, but also on research topics with practical applications, such as talent development, performance analysis, and psychological topics.…”
Section: Introductionmentioning
confidence: 99%
“…Do ponto de vista prático, o presente estudo contribui com pessoas envolvidas com o handebol em nível escolar (e também demais níveis), como professores/treinadores, gestores e organizadores de competições, já que, uma vez que estes profissionais entendam o EIR, poderão repensar suas práticas e as políticas do esporte, fazendo com que os processo de seleção, escalação e competição de estudantes-atletas possam proporcionar oportunidades igualitárias de crescimento e desenvolvimento no esporte. Nesse sentido, estudos têm proposto divisões das categorias existentes e consideração da maturação biológica (CASTRO et al, 2022a).…”
Section: Considerações Finaisunclassified
“…O Efeito da Idade Relativa (EIR) refere-se à prática de agrupamento dos atletas em coortes anuais com base nas suas datas de nascimento (CASTRO et al, 2022a;GOLDSCHMIED, 2011), o que afeta a seleção destes por conta das diferenças previstas entre atletas nascidos nos primeiros meses do ano quando comparados a atletas nascidos nos últimos meses (CASTRO et al, 2022b;CASTRO et al, 2023). Ou seja, aqueles atletas nascidos no primeiro semestre do ano seriam maturacional, física e mentalmente mais desenvolvidos do que os nascidos no segundo semestre (BABIĆ et al, 2022).…”
Section: Introductionunclassified